PANCASILA, DEMOCRACY, AND NKRI BER-SHARĪ’AH IN INDONESIA: HOW CHRISTIANS SHOULD RESPOND AND PARTICIPATE - Andreas Jonathan, (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2022)
Democracy, pluralism, Pancasila, and religious freedom become a heated debate in Indonesia because they are not only theoretical and conceptual but also have a significant influence on many aspects of the nation’s life. Moreover, the demand for the implementation of sharī’ah from a small number of Muslim groups continues to echoe in this country which, off course, concern also the Christians who become the second largest population in this country. This paper is an attempt to examine the Christians’ participation in democracy and Pancasila amids the demand for the implementation of sharī’ah in Indonesia. It discusses theological perspectives for Christians’ participation in the public space, a brief history of the struggle on sharī’ah law and Pancasila, and how Christians have and should respond through civil society. The paper argues that Christians can participate in many ways in democratization and defending Pancasila in Indonesia through the channels of civil society.